2019
DOI: 10.3390/molecules24081621
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Novel Purification Process of PANI and PANI/AgNPs Composite

Abstract: In this work, polyaniline (PANI) is synthesized via oxidative polymerization of aniline and purified using organic solvents where the emeraldine phase is isolated by employing a phase separation system. The above contributes to the increase in the percentage yield compared to previous works and the possibility of being used as a single phase. In addition, the PANI/AgNPs composite is prepared in situ at the polymerization of aniline, adding silver nitrate and glycine to create the AgNPs inside the PANI matrix b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…The C=C stretching of aromatic rings for ABA showed the peaks at 1603 and 1587 cm −1 , while PABA showed the peak at 1487 cm −1 . The C=C and C=N stretching of quinoid rings for PABA exhibited the significant peak at 1580 cm −1 , which indicated that the synthesized PABA was composed of amine units [ 41 , 42 ]. The other significant peaks at 1291 and 1059 cm −1 for ABA and 1228 and 1040 cm −1 for PABA corresponded to C–N stretching of the aromatic ring and aliphatic amine, respectively [ 38 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The C=C stretching of aromatic rings for ABA showed the peaks at 1603 and 1587 cm −1 , while PABA showed the peak at 1487 cm −1 . The C=C and C=N stretching of quinoid rings for PABA exhibited the significant peak at 1580 cm −1 , which indicated that the synthesized PABA was composed of amine units [ 41 , 42 ]. The other significant peaks at 1291 and 1059 cm −1 for ABA and 1228 and 1040 cm −1 for PABA corresponded to C–N stretching of the aromatic ring and aliphatic amine, respectively [ 38 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…18−20 Conductive polyaniline (PANI) is considered to be one of the most promising conductive polymers due to its lower cost, easy synthesis, reversible redox reaction, and excellent environmental stability. 21 The composite obtained by combining it with inorganic magnetic particles has both the high relative permittivity of polyaniline and the high relative magnetic permeability of magnetic inorganic particles, which makes it an ideal material for the purpose of preparing MAMs. For example, Fe 3 O 4 @PANI nanospheres fabricated by hydrothermal and oxidative polymerization have excellent electromagnetic attenuation properties, which can obtain a reflection loss of −55.5 dB.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The most used hybrid composite (conductive polymer–metal oxide) is PANI with TiO 2 which can photodegrade several pesticides, dyes, and pharmaceuticals under the irradiation of UV or visible light [ 33 , 34 ]. Nevertheless, PANI is synthesized by chemical oxidative polymerization under strongly acidic conditions at sub-zero temperatures [ 35 ]. It is important to consider the degree of oxidation of the nitrogen atoms, and PANI can be classified in three forms: fully reduced, half or fully oxidized [ 36 ].…”
Section: Introductionmentioning
confidence: 99%